Power Leakage Monitoring and Warning Device for Power Grid Fault Diagnosis: Design and Field Test - Yang, Qi; Xie, Xuegang; Huang, Jisheng; Wu, Jintao (Frontiers in Energy Research, 2022)
Electrical equipment insulation damage, metal shell conduction on rainy days, and wire short circuit are easy to produce leakage, which forms step voltage on the ground and endangers the life safety of nearby personnel. In addition to the existing leakage protector, a new method is proposed to use leakage energy to obtain energy and early warning. The step voltage generated by the leakage current is collected through the electrode, which is rectified and reduced by the nano power LTC3588, while energy is stored in the super capacitor for the superheterodyne transmitting module to send the leakage signal to the nearby receiving device. According to whether the superheterodyne transmitting module sends the leakage signal, it is judged whether leakage occurs here. The experimental results illustrate that when 10mA leakage occurs in 220V wire, the electrode distance is 1.0m, while the energy extraction device can obtain 360MW power for the superheterodyne transmitting module to send the leakage signal.